2014
DOI: 10.1590/0004-282x20130212
|View full text |Cite
|
Sign up to set email alerts
|

Suicide attempts in a emergency hospital

Abstract: The most important baseline predictors of suicide attempts (SAs) are baseline severity, the number of previous hospitalizations and the length of the current episode of depression 1 . The probability of having two or more SAs over the past year increased with the severity of substance use and violent behavior across attempter subtypes. A previous study indicates that the treatment of depressive symptoms in teen attempters remains an important goal 2 . Suicidal and nonsuicidal self-harm are both significant ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 19 publications
(13 reference statements)
1
7
0
6
Order By: Relevance
“…We underline the inversion of predominant gender with increasing age, that is, females were more prevalent in the age group over 12 years in this study. As intentional poisoning among adolescents is more frequent in females, 16 these findings raise the suspicion that some cases have been wrongly classified as accidental in this age group. The fact that benzodiazepines were disproportionately involved in this age group corroborates this suspicion (5% of victims aged up to 12 years and 13% of those over this age).…”
Section: Discussionmentioning
confidence: 99%
“…We underline the inversion of predominant gender with increasing age, that is, females were more prevalent in the age group over 12 years in this study. As intentional poisoning among adolescents is more frequent in females, 16 these findings raise the suspicion that some cases have been wrongly classified as accidental in this age group. The fact that benzodiazepines were disproportionately involved in this age group corroborates this suspicion (5% of victims aged up to 12 years and 13% of those over this age).…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide, and in the Middle East, psych-related ED visits and suicide attempts continue to grow [ 14 16 , 20 , 21 , 23 ]. Studies have shown that 1 in 4 Lebanese will suffer from mental illness in their lifetime [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2010, in Alagoas, 26% of young people (10-19 years old) were hospitalized for attempted suicide at a state hospital of reference 11 . These data are worrying and alarming, especially because of the reporting constraint.…”
Section: Introductionmentioning
confidence: 99%